(untitled) (International Journal of Environmental Sciences, 2025)
This conceptual research paper explores the amalgamation of visual cognition, color psychology and memory retention in aspects of marketing. This paper will attempt to propose a unified model drawing from various theories such as Dual-Coding Theory, Levels of Processing, and the Color-in-Context framework to explain how consumers can process, encode and retrieve visual stimuli primarily influenced by color, this paper will check for critical theoretical gaps including memory color effect, cultural variability in color interpretation and the trade off between contrast and being appropriate in design, this study will offer a foundation for future empirical studies, insights gained will most significantly have implication on various facets of marketing such as branding, advertising and digital media strategy.